Reactive Oxygen Species Produced by Mutated Mitochondrial Respiratory Chains of Entire Cells Monitored Using Modified Microelectrodes. Issue 3 (22nd January 2019) - Malferrari, Marco; Ghelli, Anna; Roggiani, Francesco; Valenti, Giovanni; Paolucci, Francesco; Rugolo, Michela; Rapino, Stefania
Abstract: Genetic alterations affecting subunits of the mitochondrial respiratory chain complexes often impair their catalytic activities and result in enhanced production of reactive oxygen species (ROS). An electrochemical setup was employed to quantify mitochondrial ROS production in plasma membrane‐permeabilized cellular models of two genetic diseases: the Δcytb cell line bearing a microdeletion in the mitochondrial MT‐CYB gene causing a severe encephalomyopathy and the RJ206 cell line, harbouring a pathogenic mutation associated with Leber's hereditary optic neuropathy. The responses of black platinum modified microelectrodes to the most common cellular redox buffers, namely, NADH and glutathione, as well as substrates deriving from the oxidative metabolism of glucose, were investigated; a relatively high sensitivity, although lower than that for ROS, was shown for NADH. Time‐resolved amperometric measurements of ROS production upon respiratory chain activation at high NADH/NAD + ratio revealed a 50 % and 100 % increase of ROS in cells bearing defective complex I and complex III, respectively, as compared to wild type cells. Abstract : The production of reactive oxygen species (ROS) by mitochondria is investigated in cellular models that are representative of two mitochondrial diseases. A three‐electrode setup, combined with a partial permeabilization of the cell plasmatic membrane, is employed to quantify mitochondrial ROS increase in these two mutant cell lines as compared to the wild‐type cells.